A reconstructing approach to end‐to‐end network traffic based on multifractal wavelet model. (12th June 2013) - Nie, Laisen; Jiang, Dingde; Guo, Lei; Xu, Zhengzheng
SUMMARY This paper studies the reconstructing method of end‐to‐end network traffic. Due to the development of current communication networks, our networks become more complex and heterogeneous. Meanwhile, because of time‐varying nature and spatio‐temporal correlations of the end‐to‐end network traffic, to obtain it accurately is a great challenge. We propose to exploit discrete wavelet transforms and multifractal analysis to reconstruct the end‐to‐end network traffic from time–frequency domain. First, its time–frequency properties can be characterized in detail by discrete wavelet transforms. And then, we combine discrete wavelet transforms and multifractal analysis to reconstruct end‐to‐end network traffic from link loads. Furthermore, our method needs to measure end‐to‐end network traffic to build the statistical model named multifractal wavelet model. Finally, simulation results from the real backbone networks suggest that our method can reconstruct the end‐to‐end network traffic more accurately than previous methods. Copyright © 2013 John Wiley & Sons, Ltd.